Experimental Fock-state bunching capability of non-ideal single-photon states - Zapletal, Petr; Darras, Tom; Le Jeannic, Hanna; Cavailles, Adrien; Guccione, Giovanni; Laurat, Julien; Filip, Radim (Optica, 2021)
Advanced quantum technologies, as well as fundamental tests of quantum physics, crucially require the interference of multiple single photons in linear-optics circuits. This interference can result in the bunching of photons into higher Fock states, leading to a complex bosonic behavior. These challenging tasks timely require to develop collective criteria to benchmark many independent initial resources.Here we determine whether n independent imperfect single photons can ultimately bunch into the Fock state jni.We thereby introduce an experimental Fock-state bunching capability for single-photon sources, which uses phase-space interference for extreme bunching events as a quantifier. In contrast to autocorrelation functions, this operational approach takes into account not only residual multi-photon components but also a vacuum admixture and the dispersion of individual photon statistics.We apply this approach to high-purity single photons generated from an optical parametric oscillator and show that they can lead to a Fock-state capability of at least 14.Our work demonstrates a novel collective benchmark for single-photon sources and their use in subsequent stringent applications.
CRIS-Team Scopus Importer:2021-06-11